Whole-genome sequencing for TB source investigations: principles of ethical precision public health. - A Van Rie; D G de Viedma; C Meehan; I Comas; T H Heupink; E De Vos; W A de Oñate; Vanessa Mathys; Pieter-Jan Ceyssens; Groenen, G; F González-Candelas; A Forier; et al. (Int J Tuberc Lung Dis, 2021)
Whole-genome sequencing (WGS) of allows rapid, accurate inferences about the sources, location and timing of transmission. However, in an era of heightened concern for personal privacy and science distrust, such inferences could result in unintended harm and undermine the public´s trust. We held interdisciplinary stakeholder discussions and performed ethical analyses of real-world illustrative cases to identify principles that optimise benefit and mitigate harm of WGS-driven TB source investigations. The speed and precision with which real-time WGS can be used to associate strains with sensitive information has raised important concerns. While detailed understanding of transmission events could mitigate harm to vulnerable patients and communities when otherwise unfairly blamed for TB outbreaks, the precision of WGS can also identify transmission events resulting in social blame, fear, discrimination, individual or location stigma, and the use of defaming language by the public, politicians and scientists. Public health programmes should balance the need to safeguard privacy with public health goals, transparency and individual rights, including the right to know who infects whom or where. Ethical challenges raised by real-time WGS-driven TB source investigation requires public health authorities to move beyond their current legal mandate and embrace transparency, privacy and community engagement.